Modulation of the glutamatergic transmission by Dopamine: a focus on Parkinson, Huntington and Addiction diseases - Gardoni, Fabrizio; Bellone, Camilla (Frontiers in Cellular Neuroscience, 2015)
Dopamine plays a major role in motor and cognitive functions as well as in reward processing by regulating glutamatergic inputs. In particular in the striatum the release of Dopamine rapidly influences synaptic transmission modulating both AMPA and NMDA receptors. Several neurodegenerative and neuropsychiatric disorders, including Parkinson, Huntington and addiction-related diseases, manifest a dysregulation of glutamate and Dopamine signaling. Here, we will focus our attention on the mechanisms underlying the modulation of the glutamatergic transmission by DA in striatal circuits.